Treatment efficacy of ribociclib or palbociclib plus letrozole in hormone receptor-positive/HER2-negative metastatic breast cancer - Kahraman, Seda; Erul, Enes; Seyyar, Mustafa; Gumusay, Ozge; Bayram, Ertugrul; Demirel, Burcin Cakan; Sendur, Mehmet Ali Nahit (Taylor & Francis Ltd, 2023)
Background: Ribociclib, palbociclib and abemaciclib are currently approved CDK4/6 inhibitors along with aromatase inhibitors as the first-line standard-of-care for patients with hormone receptor-positive, HER2-negative metastatic breast cancer. Methods: The authors report retrospective real-life data for 600 patients with estrogen receptor- and/or progesterone receptor-positive and HER2-negative metastatic breast cancer who were treated with ribociclib and palbociclib in combination with letrozole. Results & conclusion: The results demonstrated that the combination of palbociclib or ribociclib with letrozole has similar progression-free survival and overall survival benefit in real life for the patient group with similar clinical features. Specifically, endocrine sensitivity may be a factor to be considered in the treatment preference.
Keywords: CDK 4; 6 inhibitors; HER2-negative metastatic breast cancer; HR-positive; letrozole